Influence of chemical treatment on the electrical conductivity and thermopower of expanded graphite foils. Issue 7 (19th June 2013) - Rastegaralam, Mina; Piao, Mingxing; Kim, Gyutae; Dettlaff‐Weglikowska, Urszula; Roth, Siegmar
Abstract: We investigated the interaction of chemical materials with flexible graphite foils which were fabricated from the expanded graphite (EG) flakes by mechanical rolling and compressing. A variety of performed experiments demonstrated that the electrical conductivity and thermoelectric power (TEP) of the graphite foils can be modified by chemical treatments. In particular, the "as prepared" p‐type graphite foil was successfully transferred into an n‐type doped material upon a treatment with amine containing compounds. Generally, the acceptor‐like chemicals increasing the concentration of the electric charge carriers enhanced the conductivity of the graphite foils, thereby, showing a decrease in the TEP reflected by the Seebeck coefficient, whereas the donor molecules significantly affected the conductivity and changed the sign and value of the TEP. Thermal and electrical insulating polymers, such as PVDF, PMMA, PVA, PS or PC, filling the inter‐lamellar spacing reduced the conductivity of the foil due to increase of the layer‐to‐layer resistance. They also blocked heat flow in the foil, and consequently increased the Seebeck coefficient. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)